Analysis of Exploratory Factors of Entrepreneurial Fitness in the Recognition of Technological Opportunity - Jiang Hong; Zhang Xiaodan; Du Yanjie (Zhishi guanli luntan, 2017)
[Purpose/significance] Enterprise opportunity recognition is one of the key factors affecting enterprise production and innovation. In the process of technology opportunity identification, the fitness between enterprise and technological opportunity affects whether technological opportunity can enter the utilization stage from the cognitive stage. Analyzing the influential factors of entrepreneurial fitness will help companies achieve technical opportunity recognition. [Method/process] This paper adopted the method of literature review and focused on group interviews. It designed the survey scale and the questionnaire on the entrepreneurial fitness in technology opportunity identification. Then, by using the SPSS 21.0, it analyzed collected data. [Result/conclusion] The results show that the entrepreneurial fitness can be analyzed from two dimensions of enterprise innovation ability and enterprise knowledge sharing ability in the technology opportunity recognition process. After the principal component analysis, four first-order variables are created in the category of enterprise innovation ability and three first-order variables were created in the category of the enterprise knowledge sharing ability. In summary, the factor structure of entrepreneurial fitness in the enterprise opportunity recognition is obtained.